Degassing and Cycling of Mercury at Nisyros Volcano (Greece). (14th August 2019) - Gagliano, A. L.; Calabrese, S.; Daskalopoulou, K.; Cabassi, J.; Capecchiacci, F.; Tassi, F.; Bellomo, S.; Brusca, L.; Bonsignore, M.; Milazzo, S.; Giudice, G.; Li Vigni, L.; et al.
Abstract : Nisyros Island (Greece) is an active volcano hosting a high-enthalpy geothermal system. During June 2013, an extensive survey on Hg concentrations in different matrices (fumarolic fluids, atmosphere, soils, and plants) was carried out at the Lakki Plain, an intracaldera area affected by widespread soil and fumarolic degassing. Concentrations of gaseous elemental mercury (GEM), together with H2 S and CO2, were simultaneously measured in both the fumarolic emissions and the atmosphere around them. At the same time, 130 samples of top soils and 31 samples of plants ( Cistus creticus and salvifolius and Erica arborea and manipuliflora ) were collected for Hg analysis. Mercury concentrations in fumarolic gases ranged from 10, 500 to 46, 300 ng/m 3, while Hg concentrations in the air ranged from high background values in the Lakki Plain caldera (10-36 ng/m 3 ) up to 7100 ng/m 3 in the fumarolic areas. Outside the caldera, the concentrations were relatively low (2-5 ng/m 3 ). The positive correlation with both CO2 and H2 S in air highlighted the importance of hydrothermal gases as carrier for GEM. On the other hand, soil Hg concentrations (0.023-13.7 μ g/g) showed no significant correlations with CO2 and H2 S in the soil gases, whereas it showed a positive correlation with total S content and an inverse one with the soil pH, evidencing the complexity of the processes involving Hg carried by hydrothermal gases while passing through the soil. Total Hg concentrations in plant leaves (0.010-0.112 μ g/g) had no direct correlation with soil Hg, with Cistus leaves containing higher values of Hg with respect to Erica . Even though GEM concentrations in the air within the caldera are sometimes orders of magnitude above the global background, they should not be considered dangerous to human health. Values exceeding the WHO guideline value of 1000 ng/m 3 are very rare (<0.1%) and only found very close to the main fumarolic vents, where the access to tourists is prohibited.